Clinico-haematobiochemical profile in chronic anemic crossbred cattle - BHARDWAJ, R K; RANDHAWA, C S; RANDHAWA, S S; DHALIWAL, P S (The Indian Journal of Animal Sciences, 2010)
Crossbred cows (250) of 3–9 years of age, were screened for gastrointestinal parasites and blood protozoan/rickettesia and acid-fast bacilli (AFB) in faeces. Anemic, apparently healthy crossbred cows (43), negative for gastrointestinal parasites, AFB in faecal smears and protozoa/rickettesia in blood smear were finally sampled to establish the etiology of chronic anemia in crossbred cows. The blood samples were analyzed for haematological parameters, viz. Hb, PCV, TEC, red cell indices, red cell morphology and regenerative response in blood smear. Bone marrow aspirate examination was done to calculate M:E ratio and to assess iron stores in ten anemic cows to see regenerative response. Blood was also analyzed for biochemical parameters, viz. iron biochemistry, total bilirubin, TPP, albumin, globulin, A:G ratio, fibrinogen, PUN and TPP:Fib. ratio. Anemia was mild in 55.8%, moderate in 30.3% and severe in 13.9% of crossbred cows. Normal plasma iron and normal TIBC was observed in 55.9% of anemic cows. Hypoproteinemia and hypoalbuminemia was detected in only 4.65% cows, low A:G ratio in 16.3% and low TPP: Fib. ratio in 11.6% of anemic cows. Plasma urea nitrogen was significantly low in anemic cows. Mean M:E ratio was low (0.6±0.05) in anemic as compared to non-anemic (1.02±0.03) cows suggestive of regenerative anemia . Bone marrow stores were adequate in 7 and low in 3 anemic cows. Considering morphology of red cell, iron biochemistry, A:G and TPP:Fib. ratio, tentative diagnostic possibilities of idiopathic chronic anemia was evolved as anemia of chronic inflammatory diseases in 30.2%, early iron deficiency in 16.3%, iron deficiency in 9.3%, nutritional factors other than iron in 16.3% and etiology was obscure in 9.3% of chronically anemic cows. Trypanosoma evansi infection was etiology of chronic anemia in 18.6% cows.